IMPLEMENTASI SISTEM RELY ON DALAM SINKRONISASI DATA PELANGGAN PADA PT. PGN TBK AREA SEMARANG - Az-zahra, Annisa Intan; Nahar, M.; Widyanti, Dika Vivi; Nugroho, Jati (Politeknik Negeri Semarang, 2023)
This research focuses on the implementation of the Rely On system operated by PT PGN Tbk, which is a state owned company providing services to the general public in gas sales activities. This study aims to describe the implementation of the Rely On system in synchronizing customer data and solutions to problems that occurred in 2019-2020 related to customer data errors. This final project is written descriptively, with the research methods used are interviews, observations at PT PGN Tbk Area Semarang and literature study. This study uses the TAM approach to determine perceptions of ease and usability in implementing the Rely On PGN system. The difficulty of finding customer data to make payments is a problem faced by the company. Solutions owned by the company can provide innovative or sophisticated features in the Rely On system, implement periodic data control, and provide suggestions to the central office to link all data from sub-districts, RT, RW so that data searches are easier to do. The result of this research is that thecompany's image as a service provider is getting better.